Jornalismo e narrativas transmidias: a reportagem no contexto da convergência - Araujo, Yuri Borges de (2014)
The transmedia storytelling is a phenomenom recently conceptualized theoretically (JENKINS, 2009), arising from ficcional mediatic products and disseminated as well by the use on other fields. This search aims to analyze how the transmedia storytellings can be applied to journalism on the basis of an specific genre, the reporting. To that, take as reference theoretical developments performed by brazilian authors (FECHINE et al., 2011, 2012, 2013), on the basis of televisive fiction, which culminated on concepts as transmediation and transmedia contents and deepened the comprehension and the research in this area. Thenceforth, this study propone a problematization and apropriation of this theoretic support for the journalism field, using, for that, a comprehension of journalistic production on a speech level, as well as its social practices (newsmaking). The empiric research also take two different paths. First, analyze a group of reportings, in which there is transmediation, in order to verifying the configuration of the transmedia phenomenom - more specifically of the transmedia storytelling - and its particularities to journalism. Then, develops an investigation, based on the etnographic method, of the productive routine on the special reporting section of the Jornal do Commercio (Recife/PE), aiming to investigate the conditions of transmediation in this range and the practices that favor and difficult the employment of transmedia storytelling. The result are, therefore, compared and related, with the goal of providing multidimensional view of the phenomenom